The changing landscape of school leadership: recalibrating the school principalship - Norton, M. Scott (Rowman & Littlefield Publishers, 2015)
The primary focus of the book is to emphasize the major changes in the leadership responsibilities of the school principal and to underscore the necessity for them to gain new knowledge and skills in order to direct their leadership toward meeting the new changes in school-community goals and objectives. M. Scott Norton emphasizes the fact that contemporary issues and problems must be viewed as symptoms of change. The symptoms represent administrative tasks that must be attacked by implementing the primary reason that the school principal is hired, that of leading on-going change.